Randomized Crossover Study of Auricular Plaster Therapy to Relieve Dental Anxiety in Children - Wang, Jiangtao; Zhang, Jie; Sun, Dalei (Frontiers in Psychiatry, 2022)
Objective: To determine if auricular plaster therapy (APT) can alleviate dental anxiety in children aged 9 or 10 years old. Methods: A crossover research was conducted on children with at least two deep-arrested deciduous molar caries (N = 80?). The first group (N = 40) received APT intended to reduce anxiety prior to the first caries treatment, whereas the second group (N = 40) received placebo/control APT (no anticipated impact on anxiety). The APT approaches were exchanged after a washout period following the initial caries treatment. Additionally, both groups were also informed and given a demonstration regarding the procedures and equipment prior to their use as part of a Tell-Show-Do (TSD) protocol. The dentists, children, and parents were all involved in assessing the level of anxiety using general anxiety scales. Moreover, the average heart rate and salivary cortisol concentration, both of which are indications of anxiety, were compared between the pre- and post-intervention periods. The participants were unaware of the type of APT that was employed (anti-anxiety vs. control). To avoid inadvertently influencing the outcome, all psychologists, investigators, and data recorders were blinded to the randomized subject sequence. Results: Children treated with anti-anxiety APT demonstrated significantly higher levels of obedience than children treated with control APT (P<0.05). In addition, children treated with APT had a lower average heart rate while awaiting treatment, undergoing local anesthesia, and receiving dental caries treatment (P<0.05). These children had reduced salivary cortisol levels while awaiting treatment (P<0.05). Conclusion: Anti-anxiety APT can help relieve dental anxiety in children. [Keywords] Child dental anxiety; auricular-plaster therapy; trait anxiety; non-trait anxiety; acupressure